A Robust Carbon Nanotube and PVDF‐HFP Nanofiber Composite Superwettability Membrane for High‐Efficiency Emulsion Separation. Issue 10 (8th April 2020) - Wang, Yaqiong; Yue, Guichu; Li, Dianming; Hou, Lanlan; Zhao, Xiaochen; Cui, Zhimin; Bai, Jie; Wang, Nü; Zhao, Yong
Abstract: Oil or chemical purification is significant not only for industrial safety production but also because it conforms to the principle of sustainable development. In this paper, based on the synergistic concept of superwettability and nanopores sieve effect, a superoleophilic and under‐oil superhydrophobic carbon nanotube/poly(vinylidene fluoride‐ co ‐hexafluoropropylene) nanofiber composite membrane is prepared via electrospinning, pressure‐driven filtration, and chemical vapor modification. The as‐prepared membrane with durable mechanical and chemical stabilities achieves separation efficiency higher than 99.9% and high flux up to 632.5 L m −2 h −1 bar −1 for different water‐in‐oil emulsions. This membrane is highly promising for the petroleum and chemical industries for both product quality improvement and green recycling manufacturing processes. Abstract : A carbon nanotubes/poly(vinylidene fluoride‐ co ‐hexafluoropropylene) nanofibers composite emulsion separation membrane, which exhibits superoleophilic properties and under oil superhydrophobic properties with appropriate nanosize pores, can achieve a water‐in‐oil emulsion separation efficiencies above 99.9%, and higher flux up to 632.5 L m −2 h −1 bar −1 . The membrane also possesses good mechanical and chemical stabilities, making it promising for oil treatment and purification.